2014
DOI: 10.1093/icvts/ivu263
|View full text |Cite
|
Sign up to set email alerts
|

Totally robotic atrial septal defect closure: 7-year single-institution experience and follow-up

Abstract: ASD can be performed safely and effectively on an arrested or beating heart with the assistance of robotic technology. This totally endoscopic approach represents an option for patients seeking a reliable, minimally invasive ASD repair with an excellent long-term result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
59
3
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 13 publications
3
59
3
1
Order By: Relevance
“…Patients had a shorter length of hospital stay and no documented complications, which is in accordance with the literature (21). The less common procedures in this series also benefited from robotic assistance.…”
Section: Discussionsupporting
confidence: 87%
“…Patients had a shorter length of hospital stay and no documented complications, which is in accordance with the literature (21). The less common procedures in this series also benefited from robotic assistance.…”
Section: Discussionsupporting
confidence: 87%
“…[4][5][6][7] Surgical ASD closure is traditionally performed using sternotomy or thoracotomy incisions. Majdalany et al [2] reported that adult patients with Down syndrome could undergo cardiac surgery with a low risk of mortality and acceptable morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…As an alternative approach, robotic surgery can be an alternative option with a negligible operative risk, low morbidity, and early return to daily activities in Down syndrome. [4][5][6][7] …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the introduction of these advances, cosmetic and functional satisfaction with surgical outcomes have become more important. [1] To date, many different techniques have been described for cosmetic concerns such as full sternotomy with limited skin incision, [2] right anterolateral thoracotomy, [3,4] posterolateral thoracotomy, [5] robotic procedures, [6] a trans-xiphoid approach without a sternotomy [7] or different portaccess cardiac surgery. [8] Although cannulation of the femoral artery is the preferred method, ascending aortic cannulation is more advantageous due to the safety and cosmesis.…”
Section: Cite This Article Asmentioning
confidence: 99%